1995
DOI: 10.1680/gein.2.0014
|View full text |Cite
|
Sign up to set email alerts
|

Strain Behaviour of Polymeric Geogrids Subjected to Sustained and Repeated Loading in Air and in Soil

Abstract: The stress transfer mechanism in uniaxially and biaxially stretched polymeric geogrids are largely dependent on the interlocking mechanism between the soil and reinforcement. Over the years, this mechanism which may be termed the static interlock mechanism, has been researched and gained wide recognition. When pre-stretched polymeric geogrids are subjected to repeated loading cycles such as compaction forces, a second mechanism which may be termed the dynamic interlock mechanism is developed. In this paper, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…6 shows the effect of position of one geogrid reinforcement layer on the relation between the rut depth and the number of load cycles, test series II. The results concluded that the optimum position of one geogrid reinforcement layer is at the upper quarter of the base course layer and not at the interface as previously showed by Barksdale et al, (1989), Chan et al, (1989), Degroot (1986), McGown and Andrawes (1977) and Rowshanzamir and Karimian (2016).…”
Section: Resultssupporting
confidence: 70%
“…6 shows the effect of position of one geogrid reinforcement layer on the relation between the rut depth and the number of load cycles, test series II. The results concluded that the optimum position of one geogrid reinforcement layer is at the upper quarter of the base course layer and not at the interface as previously showed by Barksdale et al, (1989), Chan et al, (1989), Degroot (1986), McGown and Andrawes (1977) and Rowshanzamir and Karimian (2016).…”
Section: Resultssupporting
confidence: 70%
“…The onset of the secondary creep stage is detected at approximately 10% of creep strain. It should note that the 10% of creep strain has been reported as ''performance limit strain'' for the HDPE geogrid by Den-Hoedt (1986), Ingold et al (1994) and McGown et al (1995). The onset of tertiary creep stage is observed at approximately 60% of creep strain, which then leads to creep rupture.…”
Section: Creep Stages Of Pet and Hdpe Geogridsmentioning
confidence: 92%
“…The earliest attempt to characterize the load-strain time behaviour of extensible geosynthetic sheet reinforcement products under constant tensile load can be traced to the seminal work of McGown et al [1,2]. They introduced the concept of isochronous load-strain curves.…”
Section: Geosynthetic Stiffnessmentioning
confidence: 99%